Define $$\psi(x)=\begin{cases} 1-p & x < 0 \\ 0 & x=0 \\ -p & x> 0 \end{cases}$$. I have to show that if $$E\psi(x-\theta)= 0 $$ then $$P(X< \theta) \leq p \leq P(X \leq \theta)$$.

Any hints will be appreciated. What I have done so far is to state

$$E\psi(x-\theta)= \int_{-\infty}^\theta{(1-p)f(x)dx} - p \int_\theta^{\infty} {f(x)dx} = 0$$

Then what I get is that

$$\int_{-\infty}^\theta{(1-p)f(x)dx} = p \int_\theta^{\infty} {f(x)dx}$$

But this doesn't help much

  • $\begingroup$ Are you sure there aren't typographical errors in your definition of $\psi$? After all, except at $x=0$ your definition implies $\psi(x) \ge \min(p, 1-p) \gt 0,$ whence (assuming $0 \lt p\lt 1$ and $X$ is not just a constant), $$E(\psi(X-\theta)) \ge \min(p,1-p)(1-\Pr(X=\theta)) \gt 0,$$ whence it is never the case that $E(\psi(X-\theta))=0.$ One way to ensure the result would be to set $\psi=p$ for positive values and $\psi=p-1$ for negative values, as illustrated at stats.stackexchange.com/questions/102986/…. $\endgroup$
    – whuber
    Commented Oct 17, 2018 at 21:07
  • $\begingroup$ You are right, I had switched the two terms. Now it should be correct $\endgroup$
    – Daniel
    Commented Oct 17, 2018 at 21:14
  • $\begingroup$ That's better: now please fix the typographical errors in the remaining mathematical expressions! That might get you most of the way to the finish. $\endgroup$
    – whuber
    Commented Oct 17, 2018 at 21:17
  • $\begingroup$ Sorry, I fixed the integrals as well. But I'm still lost. How should approach this? $\endgroup$
    – Daniel
    Commented Oct 17, 2018 at 21:28
  • $\begingroup$ Write down $\Pr(X\le \theta)$ and $\Pr(X\gt \theta)$ in terms of $f.$ $\endgroup$
    – whuber
    Commented Oct 17, 2018 at 21:31

2 Answers 2


Your method assumes that $X$ is a continuous random variable, which is not stated as a condition of the problem. It is possible to get the result in a more general case, so long as there is some non-zero probability that $X \neq \theta$. From your stated form for $\psi$ you have:

$$\psi(X-\theta) = \mathbb{I}(X < \theta) - p \cdot \mathbb{I}(X \neq \theta).$$

Hence, taking the expected value you get the function:

$$\begin{equation} \begin{aligned} \mu(\theta) \equiv \mathbb{E}(\psi(X-\theta)) &= \mathbb{P}(X < \theta) - p \cdot \mathbb{P}(X \neq \theta). \\[6pt] \end{aligned} \end{equation}$$

Now, for the case where $\mathbb{P}(X \neq \theta)=0$ you have $\mu(\theta)=0$ for any $p \in \mathbb{R}$, so the implication you want to prove is not present in that case. For the case where $\mathbb{P}(X \neq \theta)>0$ the expected value condition $\mu(\theta)=0$ implies that:

$$p = \frac{\mathbb{P}(X < \theta)}{1-\mathbb{P}(X = \theta)}.$$

With a bit of algebra you can obtain the required inequalities. The first is established by:

$$\begin{equation} \begin{aligned} p = \frac{\mathbb{P}(X < \theta)}{1-\mathbb{P}(X = \theta)} \geqslant\mathbb{P}(X < \theta). \end{aligned} \end{equation}$$

The second is established as:

$$\begin{equation} \begin{aligned} p &= \frac{\mathbb{P}(X < \theta)}{1-\mathbb{P}(X = \theta)} \\[6pt] &\leqslant \frac{\mathbb{P}(X < \theta) + \mathbb{P}(X = \theta) \cdot \mathbb{P}(X > \theta)}{1-\mathbb{P}(X = \theta)} \\[6pt] &= \frac{\mathbb{P}(X < \theta) + \mathbb{P}(X = \theta) \cdot (1-\mathbb{P}(X < \theta)-\mathbb{P}(X = \theta))}{1-\mathbb{P}(X = \theta)} \\[6pt] &= \frac{\mathbb{P}(X < \theta) + \mathbb{P}(X = \theta) - \mathbb{P}(X = \theta)\mathbb{P}(X < \theta)-\mathbb{P}(X = \theta)^2}{1-\mathbb{P}(X = \theta)} \\[6pt] &= \frac{(\mathbb{P}(X < \theta) + \mathbb{P}(X = \theta)) \cdot (1 - \mathbb{P}(X = \theta))}{1-\mathbb{P}(X = \theta)} \\[6pt] &= \mathbb{P}(X < \theta) + \mathbb{P}(X = \theta) \\[8pt] &= \mathbb{P}(X \leqslant \theta). \\[6pt] \end{aligned} \end{equation}$$

  • $\begingroup$ Thanks! Can you clarify he first equation that you have above? $\endgroup$
    – Daniel
    Commented Oct 17, 2018 at 22:15
  • $\begingroup$ The symbol $\mathbb{I}$ is referring here to the indicator function which takes on a value of one if the argument statement is true, and a value of zero if it is false. So you will see that this expression of the function is equivalent to your case-based expression. $\endgroup$
    – Ben
    Commented Oct 17, 2018 at 22:19
  • $\begingroup$ Got it! Thanks. So, from the last equation I get that $P(X<\theta)<p$ but I can't get the $P(X \leq \theta)$. I try simply adding $P(X = 0)$ to get it after rearranging the equation on both sides but it doesn't help.. Any hints? $\endgroup$
    – Daniel
    Commented Oct 17, 2018 at 22:30
  • $\begingroup$ This part requires a bit of algebra. Can you show that $b/(1-a) \leqslant b+a$ when $a+b \leqslant 1$? $\endgroup$
    – Ben
    Commented Oct 17, 2018 at 22:32
  • $\begingroup$ No, I just can't get it... $\endgroup$
    – Daniel
    Commented Oct 17, 2018 at 23:12

There are many ways to approach this problem.

The point of the following is to take you through a process of analyzing the question, performing the requisite calculations as simply and easily as possible, developing a strategy to carry out the proof, and applying that strategy. A section of concluding remarks highlights what has been achieved by this method.


Recall that a random variable $X$ assigns a number to each element $\omega$ of a sample space $\Omega.$

The expression $Y=\psi(X-\theta)$ is another way to assign numbers to elements of $\Omega;$ namely, for each $\omega,$ compute $\psi(X(\omega)-\theta).$

Notice that the resulting number is one of at most three values: $-p, 0,$ and $1-p.$ As you will see, we will be able to compute the probabilities of any subset of these values. This makes $Y$ a random variable, too: and it's a discrete one. This simplifies the calculations we might need to do.

At this point it is evident we need to accomplish two things: (1) we need to compute an expectation and (2) we will need to manipulate inequalities algebraically. Let's take these in turn.

Preliminary calculations

The expectation of $Y$ can be found from the very definition: multiply its values by its probabilities. Let's tabulate them:

  1. For $X \lt \theta,$ $Y=\psi(X-\theta) = 1-p.$ This has probability $\Pr(X\lt \theta).$

  2. For $X=\theta,$ $Y=\psi(0) = 0.$ This has probability $\Pr(X=\theta).$

  3. For $X \gt \theta,$ $Y = -p.$ This has probability $\Pr(X \gt \theta).$

The expectation of $Y$ is the sum of its values times their probabilities:

$$\mathbb{E}(\psi(X-\theta)) = \mathbb{E}[Y] = (1-p)\Pr(X\lt\theta) + 0\Pr(X=\theta) + (-p)\Pr(X \gt \theta).\tag{1}$$

Strategy for the proof

The simplest way to carry out the required demonstration is to show its contrapositive: that is,

if $\Pr(X \lt \theta)\gt p$ or $\Pr(X \le \theta) \lt p,$ we need to conclude that $\mathbb{E}(\psi(X-\theta))$ is not zero.

In the first case where $\Pr(X\lt \theta)\gt p,$ the additivity of mutually exclusive events and the axiom of unit measure--two of the axioms of probability--guarantee that

$$\eqalign{ \Pr(X \gt \theta) &= 1 - (\Pr(X\lt\theta) + \Pr(X=\theta)) \\ &\le 1 - \Pr(X\lt \theta)\\ & \lt 1-p. }$$

Substituting these two inequalities into $(1)$ gives

$$\eqalign{ \mathbb{E}(\psi(X-\theta)) &= (1-p)\Pr(X\lt\theta) -p\Pr(X \gt \theta) \\ &\gt (1-p)p - p(1-p) = 0, }$$

proving the expectation cannot be zero. The demonstration in the second case parallels this one, QED.


Because this proof is completely elementary--it relies only on the definition of expectation and axioms of probability--it reveals how little needs to be assumed and how general the result is:

  1. It is not necessary to assume $0\lt p\lt 1:$ the assertion that was proved is true for all $p.$

  2. This demonstration works even when $p=0$ or $1-p=0$ (whereas other attempts might fail for these values, in case they appear in the denominators of any fractions).

  3. It was not necessary to assume $X$ has a density $f.$

  4. No higher mathematical concepts, such as integration, were needed.

  5. Indeed, we did not even have to use a distribution function for $X$: we worked directly with the relevant probabilities.

  • $\begingroup$ A good answer (+1), but I think there is presently an error. In the case where $\mathbb{P}(X=\theta) = 1$ and $p>1$, the antecedent conditions for your theorem statement are met, but you get zero expectation. I recommend actually going through the second case explicitly to deal with this. (You actually need an exclusion on this case in the theorem.) $\endgroup$
    – Ben
    Commented Oct 18, 2018 at 22:55
  • 1
    $\begingroup$ Thank you, @Ben, for taking such a close look. That nicety does need to be addressed in the second case (which I have left to the reader) and evidently I was too glib in implying nothing goes wrong then. In the portion I have explicitly presented, because it is never the case that $\Pr(X\lt\theta) \gt p \gt 1,$ I don't see any problem. Perhaps I'm overlooking something obvious. $\endgroup$
    – whuber
    Commented Oct 19, 2018 at 11:45
  • 1
    $\begingroup$ I think this is just a case where the OP needs to restate the result to rule out that special case. That case is the only one that causes problems, so it is just a matter of ruling it out in the theorem. In any case, I really like your approach to the proof (i.e., demonstrating the contrapositive). $\endgroup$
    – Ben
    Commented Oct 20, 2018 at 2:04

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.